Effects of realistic topography on the ground motion of the Colombian Andes – A case study at the Aburrá Valley, Antioquia. Issue 3 (3rd February 2016) - Restrepo, Doriam; Bielak, Jacobo; Serrano, Ricardo; Gómez, Juan; Jaramillo, Juan
Abstract: This paper presents a set of deterministic 3-D ground motion simulations for the greater metropolitan area of Medellín in the Aburrá Valley, an earthquake-prone region of the Colombian Andes that exhibits moderate-to-strong topographic irregularities. We created the velocity model of the Aburrá Valley region (version 1) using the geological structures as a basis for determining the shear wave velocity. The irregular surficial topography is considered by means of a fictitious domain strategy. The simulations cover a 50 × 50 × 25 km 3 volume, and four M w = 5 rupture scenarios along a segment of the Romeral fault, a significant source of seismic activity in Colombia. In order to examine the sensitivity of ground motion to the irregular topography and the 3-D effects of the valley, each earthquake scenario was simulated with three different models: (i) realistic 3-D velocity structure plus realistic topography, (ii) realistic 3-D velocity structure without topography, and (iii) homogeneous half-space with realistic topography. Our results show how surface topography affects the ground response. In particular, our findings highlight the importance of the combined interaction between source-effects, source-directivity, focusing, soft-soil conditions, and 3-D topography. We provide quantitative evidence of this interaction and show that topographic amplification factors can be as high as 500 per cent at some locations. In other areas within the valley, the topographic effects result in relative reductions, but these lie in the 0–150 per cent range.